Pengaruh Emotional Bias terhadap Keputusan Pendanaan BUMDes di Jawa Tengah dengan Keseimbangan Investasi Berbasis Imbalan sebagai Variabel Mediasi - Astohar Astohar; Dhian Andanarini Minar Savitri; Willyanto Kartiko Kusumo; Emi Wardati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The Village-Owned Enterprises (BUMDes) play a strategic role in enhancing the village economy by utilizing the potential within the village. One of the main challenges faced by BUMDes is the issue of capital, which affects the ability of businesses to grow and achieve their shared goals. This study aims to analyze the effect of emotional bias on investment decisions with reward-based investment balance as a mediating variable. This study used a sample of 108 BUMDes scattered across six regions in Central Java. The sampling method employed was a combination of purposive sampling and cluster sampling, where the selected BUMDes represent specific regions and involve investors from the community or community groups. Data were collected from BUMDes in six regions (administrative areas) in Central Java. The analysis tools used in this study include simple regression, multiple regression, and the Sobel test for mediation, supported by normality tests, classical deviation tests, and coefficient of determination. The results showed that emotional bias significantly affected the investment decisions of the community (t = 3.034; sig = 0.000) and also influenced the reward-based investment balance (t = 4.256; sig = 0.000). Additionally, the reward-based investment balance variable was proven to have a direct impact on investment decisions (t = 3.190; sig = 0.000). This study also found that the reward-based investment balance variable partially mediates the effect of emotional bias on investment decisions, meaning that this effect can still be mediated by other variables. The Sobel test indicated a significant result (t = 3.104; sig = 0.000), showing that the effect of emotional bias on investment decisions can be mediated through reward-based investment balance.